Propositional idea density in older men's written language: Findings from the HIMS study using computerised analysis. (February 2015) - Spencer, Elizabeth; Ferguson, Alison; Craig, Hugh; Colyvas, Kim; Hankey, Graeme J.; Flicker, Leon
Abstract Decline in linguistic function has been associated with decline in cognitive function in previous research. This research investigated the informativeness of written language samples of Australian men from the Health in Men's Study (HIMS) aged from 76 to 93 years using the Computerised Propositional Idea Density Rater (CPIDR 5.1). In total, 60 255 words in 1147 comments were analysed using a linear-mixed model for statistical analysis. Results indicated no relationship with education level (p = 0.79). Participants for whom English was not their first learnt language showed Propositional Idea Density (PD) scores slightly lower (0.018 per 1 word). Mean PD per 1 word for those for whom English was their first language for comments below 60 words was 0.494 and above 60 words 0.526. Text length was found to have an effect (p = <0.0001). The mean PD was higher than previously reported for men and lower than previously reported for a similar cohort for Australian women.